COMPUTERIZATION IN HIGHER MEDICAL EDUCATION OF THE USA AND UKRAINE (Journal of Information Technologies in Education (ITE), 2016)
The article researches the development of computer-oriented learning and information andcommunication technologies implementation in the USA, describes the state of computerization andmodernization at higher medical educational institutions of Ukraine, analyzes the experience of Danylo Halytsky Lviv National Medical University (DHLNMU), and the department of Latin and foreign languages in particular, in the sphere of new educational and Internet technologies usage for study. As the result of the study the first computerized programs used for the future physicians training have been characterized. It has been stated that for the first time computer technologies in higher medical education were used in the USA and served accessory learning function aimed at facilitating and improving pedagogical instruments and methods. Furthermore, the paper proves that information and communication technologies are commonly used as accessory learning tools by Ukrainian medical students. The process of computerization and ICTs implementation in the scope of higher medical education has been developing rapidly and has a big potential according to the results of the survey carried out at DHLNMU that are described in this paper
Keywords: computer technologies; information and communication technologies; higher medical education; computerization; Ukraine; USA; future physician